Graves’ Disease and Rheumatoid Arthritis: A Bidirectional Mendelian Randomization Study - Wu, Dide; Xian, Wei; Hong, Shubin; Liu, Boyuan; Xiao, Haipeng; Li, Yanbing (Frontiers in Endocrinology, 2021)
Background The frequent coexistence of Graves’ disease (GD) and rheumatoid arthritis (RA) has been cited and discussed in observational studies, but it remains a question as to whether there is a causal effect between the two diseases. Methods We retrieved genome-wide association study (GWAS) summary data of GD and RA from BioBank Japan (BBJ). Single nucleotide polymorphisms (SNPs) associated with diseases of interest were selected as instrumental variables (IVs) at a genome-wide significance level (P < 5.0 × 10-8). The random-effects inverse variance weighted method (IVW) was used to combine the causal effect of IVs. The horizontal pleiotropy effect was analyzed by MR Egger and weighted median method sensitivity test. A leave-one-out analysis was conducted to avoid bias caused by a single SNP. The statistical power of our MR result was calculated according to Brion's method. Results Our study discovered a bidirectional causal effect between GD and RA. The presence of RA may increase risk of GD by 38% (OR 1.38, 95% CI 1.10-1.75, P = 0.007). Similarly, GD's existence may increase risk of RA by 30% (OR 1.30, 95%CI 0.94-1.80, P = 0.112). Our study provides 100% power to detect RA's causal effect on GD risk, and vice versa. Conclusions We found a bidirectional causal effect between GD and RA in an Asian population. Our study supported the clinical need for screening GD in RA patients, and vice versa. The potential benefit of sound management of RA in GD patients (or GD in RA patients) merits excellent attention. Moreover, novel satisfactory medicine for RA may be applicable to GD and such potential is worthy of further investigation.